2016
DOI: 10.22319/rmcp.v7i1.4147
|View full text |Cite
|
Sign up to set email alerts
|

Individual lactation curves in Siboney dairy cows of Cuba

Abstract: El objetivo fue estudiar y modelar las curvas de lactancia individuales en vacas Siboney, comparando cuatro modelos matemáticos. En total, 31,631 registros de producción de leche del día de control (PDC) de 3,697 lactancias (1 a 5) provenientes de 2,632 vacas Siboney de Cuba (5/8 Holstein 3/8 Cebú Cubano) registrados mensualmente entre 1994 y 2003 se ajustaron mediante las funciones de Wood, Wilmink, Ali-Schaeffer y Polinomios de Legendre. Los parámetros se estimaron usando regresiones no lineales y la bondad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…According to Palacios Espinosa et al [ 63 ], the parameters related to the fitting performance reported by the Legendre polynomials were lower than those obtained for the Ali and Schaeffer (ALISCH) function. This behavior was referred to by Ali and Schaeffer [ 57 ], who found it difficult to find biological reasons why the functions of the Ali-Schaeffer and Legendre polynomials can detect dissimilar types of curves; however, this behavior is particularly useful for random regression analyses, where individual deviations from a curve are sought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Palacios Espinosa et al [ 63 ], the parameters related to the fitting performance reported by the Legendre polynomials were lower than those obtained for the Ali and Schaeffer (ALISCH) function. This behavior was referred to by Ali and Schaeffer [ 57 ], who found it difficult to find biological reasons why the functions of the Ali-Schaeffer and Legendre polynomials can detect dissimilar types of curves; however, this behavior is particularly useful for random regression analyses, where individual deviations from a curve are sought.…”
Section: Discussionmentioning
confidence: 99%
“…According to Palacios Espinosa et al [ 63 ] and Buttchereit et al [ 49 ], the Ali and Schaeffer (ALISCH) and Legendre models presented better-fitting properties than Wilmink’s exponential (WILMINK) model for fat, protein, and dry matter. These better-fitting properties may base on the better adjustment to the distribution patterns, indicating that the models with fewer parameters find more difficulty to model the variation occurring along the entire curve.…”
Section: Discussionmentioning
confidence: 99%
“…Lactation curve can be defined as a biological process explained by a mathematical equation. It is useful for forecasting total production, for planning herd management using a reliable prediction tool, and for selecting animals considering the relationships among the different parts of the curve (Espinosa et al, 2016;Vinay-Vadillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%